Mobilização social a partir de um rio urbano da Amazônia: o processo comunicativo do Movimento Tucunduba Pró Lago Verde em Belém-Pará - RIBEIRO, Mariana Guimarães Campos (Universidade Federal do Pará, 2023)
At Belém do Pará, in a territorial context of modernization that distances us from the cycles of Nature and living spaces, the struggle for the right to the city has been intensifying since the 1970s. the Tucunduba Pro Lago Verde Movement, made up of a group of residents of the Terra Firme neighborhood, who have a history of fighting for territory. In the same year of its emergence, a left-wing government came to power in Belém and the movement saw a political opportunity to boost its mobilization for the guarantee of socio-environmental rights with the creation of Tá Selado, the Permanent Forum of Citizen Participation. The objective of this research is to understand how the communicative mobilization processes of the Tucunduba Pró Lago Verde Movement (MTPLV) contribute to the advancement of socio-environmental guidelines in Belém-PA. Social mobilization is taken here as a communicational phenomenon, being understood as a place of encounter and dialogue that makes possible the relationship of different experiences and worldviews, being able to guide the action of the subjects, by tensioning and rebelling against the hegemonic powers in the scope from the city. This research was carried out based on the participatory research methodology (PERUZZO, 2003), inspired by urban ethnography (RODRIGUES, 2006; VELHO, 2003). In the end, it was concluded that the MTPLV has not only been one of the most prominent social actors in the environmentalization of the right to the city agenda in Belém, but has also been reimagining this territory, against the dominant logic of its occupation and expansion